Andean Grains and Their Strategic Role in Sustainable Food Systems - Cunurana Cruz, Maddy Bertha (2025)
Andean grains (AG), recognized for their nutritional value and adaptability, have regained relevance as strategic crops in response to current sustainability and food security challenges. This study aimed to map the evolution, impact and trends of the scientific production focused on these crops. A scoping review based on Scopus was carried out, complemented by a bibliometric analysis using VOSviewer and Bibliometrix. The results show an increase in publications since 2012, reaching a peak in 2024 with 283 documents. Quinoa gathers the largest share of scientific output, followed by amaranth, while cañihua and tarwi receive less attention. China, India and the United States lead in publication volume and citations. In contrast, Peru, despite being a center of origin, shows a lower average impact per article. The main thematic areas include nutrition, functional foods and food security. Food Chemistry and Foods stand out as the most influential journals. Although academic interest in AG continues to grow, challenges remain related to commercialization, equitable distribution of benefits and the protection of ancestral knowledge, along with the need to strengthen interdisciplinary research across the entire value chain.